Effect of intensive interval training on red blood corpuscles and cardiovascular endurance - Sharma, S.; Singh, D. (International Journal of Sports Science and Engineering, 2012)
The purpose of the present study was to investigate the effect of intensive interval training on the nature of red blood corpuscles count and cardiovascular endurance. Interval training stresses not only the energy system but the muscular system also. To fulfil the objectives of the study, fifty students from the Department of Physical Education, Lovely Professional University, Punjab were selected to act as subjects. They were divided into two groups of twenty five each i.e. control and experimental group. Data was collected prior and after twelve weeks of training. Comparison of pre-test and post-test training data was done with the application of t-test. Statistically insignificant difference was found between the pre and post-test count of RBC`s whereas statistically significant difference was observed between pre-test and post-test data of cardiovascular endurance after twelve weeks of intensive interval training.